Sicklepod [Senna obtusifolia (L.) H. S. Irwin & Barneby] “Getting sleepy?” - Sosnoskie, Lynn M; Steckel, Sandy; Steckel, Lawrence E (Weed technology, 2021)
There is a Reaper, whose name is Death, And, with his sickle keen, He reaps the bearded grain at a breath, And the flowers that grow between. – Henry Wadsworth Longfellow, “The Reaper and the Flowers” I love sleep. My life has a tendency to fall apart when I'm awake, you know. – Ernest Hemingway